Evaluating the Effects of Artificial Intelligence and Digital Marketing on Consumer Behaviour: A Bibliometric Approach - Srivastav, Saransh Kumar; Habil, Mahima; Thakur, Pooja (Manunggal Halim Jaya, 2025)
This study examines the evolution and emerging trends in consumer behavior by integrating Artificial Intelligence (AI), digital marketing, and consumer buying behavior through bibliometric analysis. Using data from the Web of Science (2014–2023), 645 articles were analyzed to identify publication trends, key themes, and leading contributors. Bibliometric indicators, including citation counts and keyword analysis, were visualized using VOSviewer. The analysis revealed six keyword clusters, highlighting key areas such as AI-driven data analytics, customer experience, and conversational AI. The findings provide valuable insights into how AI and digital marketing influence consumer behavior, offering directions for future research. The conclusion synthesizes the key findings and outlines potential research avenues at the intersection of AI, digital marketing, and consumer behavior. This study contributes to the field by providing a comprehensive bibliometric analysis, identifying major trends, influential authors, contributing countries, and dominant themes while suggesting areas for further exploration.